2016
DOI: 10.1016/j.leukres.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of CD30-positive systemic mastocytosis with brentuximab vedotin

Abstract: Systemic mastocytosis is a myeloproliferative neoplasm with varying presentation that is caused by infiltration of neoplastic mast cells into extracutaneous tissues. Cytoreductive therapy is used to control organ dysfunction in aggressive systemic mastocytosis and is sometimes needed for control of severe refractory symptoms in patients with indolent disease. However, current standard cytoreductive agents are limited by their suboptimal degree and duration of response and associated significant toxicities, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 38 publications
1
22
0
1
Order By: Relevance
“…Recent data suggest that CD30 is expressed in human neoplastic MC and serves as a molecular target in advanced SM . Preliminary data from a small case series in human CD30‐positive mastocytosis support this hypothesis although not all patients may respond to brentuximab . In this study, we show that CD30 is also expressed in neoplastic canine MC independent of the histopathological grade.…”
Section: Discussionsupporting
confidence: 70%
“…Recent data suggest that CD30 is expressed in human neoplastic MC and serves as a molecular target in advanced SM . Preliminary data from a small case series in human CD30‐positive mastocytosis support this hypothesis although not all patients may respond to brentuximab . In this study, we show that CD30 is also expressed in neoplastic canine MC independent of the histopathological grade.…”
Section: Discussionsupporting
confidence: 70%
“…Given the reported aberrant expression of CD30 on neoplastic MC, with preferential expression in advanced SM as compared to ISM (see above) , the role of brentuximab vedotin in treating advanced SM including MCL is being currently studied (http://Clinicaltrials.gov study# NCT01807598). In a preliminary report, two of four SM patients treated with brentuximab had a response .…”
Section: Treatmentmentioning
confidence: 95%
“…Although the authors of a little case series reported some durable response [35], the role of brentuximab-vedotin in the treatment of SM is still being debated.…”
Section: New Drugsmentioning
confidence: 99%